PENGARUH INTELLECTUAL CAPITAL DAN CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN - Sari, Arum Puspita; Priyadi, Maswar Patuh (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThe purpose of this research is to find out the influence of intellectual capital and corporate governance to the corporate performance which is proxy by price to book value (PBV). The population is 142 manufacturing companies which are listed in Indonesia Stock Exchange (IDX) in 2010-2014 periods. The sample collection has been done by purposive sampling. 19 sample companies have been selected as samples based on the predetermined criteria. The data analysis has been carried out by using multiple linear regressions and SPSS (Statistical Product and Service Solutions) 23rd version application. The result of the F test shows that simultaneously all independent variables give significant influence to the corporate performance. The result of the t test shows that capital employed efficiency (CEE) and structural capital efficiency (SCE) gives positive influence to the corporate performance, but human capital efficiency (HCE) gives negative influence to the corporate performance. Meanwhile, institutional ownership and managerial ownership give negative influence to the corporate performance and independent board of commisioners give positive influence to the corporate influence.Keywords: intellectual capital, corporate governance, price to book value